2018
DOI: 10.1186/s12944-018-0791-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-protein diet for diabetic nephropathy: a systematic review of randomized controlled trials

Abstract: BackgroundA low-protein diet (LPD) is believed to be beneficial in slowing the progression of kidney disease. It is reported that low protein diet can improve protein, sugar and lipid metabolism, and reduce the symptoms and complications of renal insufficiency. However, there has been controversial regarding the effects of protein restriction on diabetic nephropathy (DN).ObjectiveTo investigate the efficacy of LPD on renal function in patients with type 1 or 2 DN by meta-analysis of randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…From the enrichment analysis, we could see that these lncRNAs in each module participated in different biological processes. DN is known to be a metabolic problem such as energy, protein and lipid disorder 24,25 . Clinical trials have suggested that nutritional and dietary interventions in DN are an essential aspect of management and patients will benefit from a strict dietary protein and carbohydrates control 26 .…”
Section: Discussionmentioning
confidence: 99%
“…From the enrichment analysis, we could see that these lncRNAs in each module participated in different biological processes. DN is known to be a metabolic problem such as energy, protein and lipid disorder 24,25 . Clinical trials have suggested that nutritional and dietary interventions in DN are an essential aspect of management and patients will benefit from a strict dietary protein and carbohydrates control 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that high protein consumption (i.e., greater than the recommended daily allowance [RDA]) may pose a health risk in certain conditions [ 1 , 2 , 3 , 4 ]; however, these concerns are not applicable to a healthy exercise-trained population. Protein restriction might play a key role in the management of chronic kidney disease (CKD) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this study has several limitations, which should be considered when interpreting its ndings. First, we did not have data on salt intake, protein intake, or levels of exercise, which would be associated with the development of diabetic nephropathy [27,[35][36][37]. In this regard, we could not clearly identify the prognostic signi cance of HBP for the development of diabetic nephropathy even in a longer study.…”
Section: Discussionmentioning
confidence: 94%